PEMANFAATAN LIMBAH KELAPA SAWIT DALAM PEMBUATAN ASAP CAIR DI DESA JEJANGKIT, BARITO KUALA - Muhammad Saukani; Jainal Arifin; Sobar Ihsan; Gusti Rusydi Furqon Syahrillah (Universitas Islam kalimantan MAB, 2017)
Jejangkit sub-district is one of the palm oil producer with the planting area of 100 ha. It was an area covered by wood Galam previously. The negative impact of oil palm development were water quality degradation and the arrival of pests so that rice production was lowered. Palm oil waste increase the income of residents around the plantation such as by utilizing oil palm shells as liquid smoke. One of program to increase the citizens income is a community service program that aims to provide information about benefit palm oil waste and provide training on making liquid smoke from oil palm waste. The partner this program is Karang Taruna Bangkit Bersama, desa Jejangkit Muara. Implementation of this program was attended by 22 members of the youth, the youth in productive age and appropriate to follow this program. The enthusiasm is felt when the program participants asked questions and demo devices pyrolysis to produce liquid smoke.